Enzyme kinetics and inhibition (Henry Stewart Talks, 2025)
Enzyme/substrate binding, Michaelis-Menten kinetics, Factors affecting enzyme activity, Types of enzyme inhibition, Allosteric enzyme regulation, Enzyme inhibitors in drug development, Enzyme regulation in metabolism and disease